Development of a core outcome set in the clinical trials of traditional Chinese medicine for diabetic foot: A study protocol - Dai, Xin Yue; Zi, Ming Jie; Liu, Chun Xiang; Wang, Yi Ming; Gao, Rui (Frontiers in Medicine, 2022)
Background:Diabetic Foot (DF) is one of the most common complications of diabetes and is associated with high morbidity, disability, lethality and low cure-rate. Traditional Chinese medicine treatment has certain characteristics and advantages in diabetic foot. Due to selective reporting bias and heterogeneity of research results, on the one hand, relevant clinical studies are of low quality and poor practicability, and on the other hand, similar studies cannot be included in meta-analysis to form high-quality evidence-based evidence and evaluate the value of studies.To solve these problems, the development of a core outcome set for traditional Chinese medicines for the treatment of diabetic foot (COS-TCM-DF) is mandatory. Methods:The COS-TCM-DF project will use established COS methodology, in four stages:(1) a scoping review and analysis of enrolled research protocols to identify and summarize all existing outcomes that have been used in trials on the prevention or treatment of diabetic foot with Chinese Medicine; (2) qualitative interviews with Diabetic foot patient and attendants to identify additional outcomes relevant to them;(3) Delphi surveys to collect opinions from key stakeholders including patients,clinical doctors,researchers，and pharmaceutical company staff and to reach a preliminary consensus;(4) a consensus meeting to develop the final COS-TCM-DF. Discussion:There is currently no COS for the measurement or monitoring of diabetic foot with Chinese medicine in trials or clinical practice.The COS-TCM-DF will be developed to facilitate the synthesis of evidence regarding the prevention and treatment of diabetic foot with Chinese medicine and to promote the consistent use of outcomes among future studies in this field.